Effect of fish density on biological production in aquaponics combining lettuce hydroponics and loach aquaculture for controlled ecological life support systems in space - Kitaya, Yoshiaki; Kawamoto, Takashige; Endo, Ryosuke; Shibuya, Toshio (Frontiers in Astronomy and Space Sciences, 2023)
There is a need to develop production technology that effectively uses limited water and other resources to create a stable food supply in space. Aquaponics, which combine hydroponics and aquaculture, is expected to be an efficient system for producing crops and animal proteins. This system sustains the reuse of water and balances nutrient elements between both cultures using dissolved elements in fish excrement for plant growth. To evaluate the effect of fish density on biological production and nitrogen usage efficiency in aquaponics combining lettuce hydroponics and loach aquaculture, we investigated the growth performance of lettuce plants and loach fish. We focused on the balance of nutrient elements, especially nitrogen flow in the system. As a result, we found that lettuce grew in aquaponics with a half-strength standard solution with an optimal combination of the number of plants and fish as well as hydroponics with a standard solution. Increasing the density of loach fish and lettuce plants can increase the total biological production of fish and plants. However, it will be important to control both fish and plant densities to increase nitrogen recovery in aquaponics with a high fish density.